Waiting for the wave, but missing the tide: Case studies of climate-related (im)mobility and health - Celia McMichael; Patricia Nayna Schwerdtle; Sonja Ayeb-Karlsson (Elsevier, 2023)
Climate change amplifies health risks, including through the health impacts of climate-related displacement. Yet diverse mobility responses in a warming world can also provide a pathway for climate change adaptation. This article examines the connections between climatic and environmental change, human mobility and health. It presents case studies across three countries: Fiji, Bangladesh, and Burkina Faso. All case studies used qualitative methods, including semi-structured interviews, storytelling, and group discussions. The Fiji case study focuses on relocation of a coastal village exposed to erosion, flooding and saltwater intrusion; it highlights self-reported health risks and opportunities following relocation. The Bangladesh case study includes seven sites that variously experience flooding, cyclones and riverbank erosion; while residents use migration and (im)mobility as a coping strategy, there are associated health risks, particularly for those who feel trapped in new sites of residence. The case study from a village in Burkina Faso examines seasonal labour migration to the Ivory Coast and Mali during times of drought and reduced agricultural productivity, and discusses health risks for men who migrate and for women who remain in sending communities. These case studies illustrate that there is no consistent figure that represents a 'climate migrant', 'climate refugee', or 'trapped' person. Accordingly, we argue that where planetary health looks to highlight 'waves' of climate displacement, it may miss the 'tide' of slower onset climatic changes and smaller-scale and diverse forms of (im)mobility. However, even where climate-related mobility is broadly adaptive - e.g. providing opportunities for livelihood diversification, or migration away from environmental risks - there can be health risks and opportunities that are shaped by socio-political contexts, access to healthcare, altered food sources, and living and working conditions. Responsive solutions are required to protect and promote the health of mobile and immobile populations in a warming world.